How does land use cover change affect hydrological response in the Atlantic Forest? Implications for ecological restoration - Lopes, Bruna Santos; Corrêa, Karlmer A. B.; Ogasawara, Matheus Eijii Kinchoku; Precinoto, Raíza Salomão; Cassiano, Carla Cristina; Sell, Bruna Moreira; Melo, Renata Siqueira; dos Reis Oliveira, Paula Caroline; Ferraz, Silvio Frosini de Barros (Frontiers in Water, 2022)
Water availability is influenced by climate conditions and physical characteristics such as topography, soil type, and land use and cover. The Atlantic Forest has a long deforestation history and shows a climatic and environmental gradient that results in natural vegetation diversity driven mainly by water availability and local conditions. Therefore, Atlantic Forest ecoregions are expected to show a natural variability of water responses and different hydrological effects caused by land-use cover change. In this study, we compared the hydrological response among 11 Atlantic Forest ecoregions in areas of native vegetation and pasture, using CHIRPS rainfall data, evapotranspiration by the MOD16A2 product of the MODIS satellite and water surplus calculated by the 19-year mass balance for 712 sampling points. The parameter “m” was calculated by equations based on the Budyko framework and varied between 1.2 and 3.6 in the biome. In 10 of the 11 ecoregions, the parameter “m” in native vegetation was statistically higher than in the pasture, and in the REST, ECOT, SEMI, STEP and PARK ecoregions this difference was more pronounced. For all ecoregions, the R/P ratio was inversely proportional to the parameter “m”, but there were different levels of variation among them. In wetter and drier areas, there is less variation in the water surplus, while the greatest variations occurred in areas where the PET/P ratio is 1.5. In conclusion, the parameter “m” of native vegetation and pasture varies in different Atlantic Forest ecoregions. The results of each ecoregion regarding hydrological response and implications for water yield can be used to understand and plan changes in land use for water production.